Niosome based transdermal film as a nanovector for the delivery of paclitaxel for skin cancer - SAIPRIYA RAMALINGAM,; HELEN ANNAL THERESE, (International Journal of Pharma and Bio Sciences, 2017)
Several topical creams to treat skin cancer have been used to deliver the drug of interest but it has been accompanied by various side effects. Novel drug delivery systems (NDDS), due to its small size and high specificity serve as a worthy opportunity for targeted drug delivery. This work aims at the synthesis and characterization of niosomes, which are phospho-lipid moieties having a 3D hollow structure. Different surfactants in various ratios were used initially to determine the best to load Paclitaxel (PTX), a chemotherapeutic drug proven to be a mitotic inhibitor. Niosomes of a uniform size of 100 nm have been synthesized on which FTIR, UV, Zeta Potential and Optical photomicrographic studies have been performed. An entrapment Efficiency (EE) of about 80.5% was achieved proving that the drug loaded niosomes have excellent pharmacokinetics. To facilitate topical application of PTX, a hydrogel was prepared using Carbopol 940 which gave a good release profile. Sustained release of drug requires constant contact to the target area, hence, in order to focus on sores which are perfused highly by tiny blood vessels, a transdermal film has been fabricated and its release has been measured.